2015
DOI: 10.1111/arcm.12217
|View full text |Cite
|
Sign up to set email alerts
|

Pottery Provenance in the Eastern Mediterranean Using Lead Isotopes

Abstract: The lead isotope composition of 45 sherds of six different pottery wares from the Eastern Mediterranean and dating from the Late Hellenistic -Late Roman period is analysed and compared to data obtained on ceramics and clays from the Eastern Mediterranean. These sherds were previously analysed by neutron activation and the origin and relationship between the wares has been debated in the literature. The results show that lead isotopes support earlier hypotheses proposed based on NAA or answer questions left una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The characterization of Sr and Nd isotopes represents an interesting, though little‐explored method that indicates the potential of radiogenic isotope analysis for determining the provenance of ancient ceramics (De Bonis et al, 2018; Kibaroğlu et al, 2019; Renson, Jacobs, et al, 2013; Renson, Martínez‐Cortizas, et al, 2013; Renson et al, 2016). The analyses conducted by the Naples group (De Bonis et al, 2018; Morra et al, 2020) tested the use of Sr and Nd isotopes for ceramic replicas made with local raw materials and archaeological pottery manufactured in the GBNR.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of Sr and Nd isotopes represents an interesting, though little‐explored method that indicates the potential of radiogenic isotope analysis for determining the provenance of ancient ceramics (De Bonis et al, 2018; Kibaroğlu et al, 2019; Renson, Jacobs, et al, 2013; Renson, Martínez‐Cortizas, et al, 2013; Renson et al, 2016). The analyses conducted by the Naples group (De Bonis et al, 2018; Morra et al, 2020) tested the use of Sr and Nd isotopes for ceramic replicas made with local raw materials and archaeological pottery manufactured in the GBNR.…”
Section: Resultsmentioning
confidence: 99%
“…They noticed that the composition of Group D is similar to ‘des sigillées chypriotes tardives’, 13 interpreted as a continuation of the Cypriot Sigillata (or Eastern Sigillata D) of Late Hellenistic to Early Roman date, due to the similarities in their chemical composition (Meyza 2007, 17–20). The results of scientific analyses (Meyza 2002; Lund 2015, 166–8; Bes 2015, 19–20; Renson et al 2016, 62–4; Hammond et al 2018, 118–19), as well as the abundance of these wares on the island, led to their being considered of Cypriot provenance 14 . Based on the evidence available so far, it is not possible to suggest a specific production location for PG 6.…”
Section: Production Groups Presentationmentioning
confidence: 99%
“…The wheel-made lamps with a biconical body in vertical section classified to PG 6 are characterised by the same elemental and mineralogical compositions as well as the appearance of fabric and surface treatment as a group of Early Hellenistic colour-coated ware pottery from the Agora (Marzec 2017, 214, Fabric Group 3), which is characterised by the same elemental composition as group D of colour-coated ware pottery distinguished by M. Picon and F. Blondé (2002, 14–15). They indicated that pottery classified to group D was produced from similar raw materials as Late Roman D/Cypriot Red Slip Ware, for which south-western Cyprus (Hayes 1967; 1985, 79; 1991, 37–8; Meyza 2002; Lund 2015, 166–8; Bes 2015, 19–20; Renson et al 2016, 62–4; Hammond et al 2018, 121) or south-western Turkey (Gunneweg, Perlman and Yellin 1983; Jackson et al 2012) were suggested as potential production locations.…”
Section: Directions Of Supplymentioning
confidence: 99%
“…For provenance studies, geochemical data are often processed by using statistical methods able to create correlation among group of samples, also in comparison with databases [6,7]. When geochemical tracers fail in group classification and provenance discrimination, recent studies have demonstrated the merits of isotopic analysis as clay provenance fingerprint [8,9]. Ceramics are the most numerous records in archaeological excavations and are often expendable for destructive analysis.…”
Section: Introductionmentioning
confidence: 99%